A Peircean approach to musicality - Ojala, Juha (Interdisciplinary Studies in Musicology, 2014)
Musicality is central to musical processes and music research. Yet, there is no consensus of what is understood by the term. It can be assumed that in large populations musicality is distributed according to a bell curve — just as any trait of personality. It is also clear that musical skills can be improved, regardless of a possible stigma of unmusicality. Depending on the conception of musicality, musicality research confronts issues and trade-offs relating to ecological validity of the concept (how musicality connects to actual music), methodology (which methods of study yield valid and reliable results), epistemology (how the gain knowledge of musicality), and ontology of music (what processes pertain to music, what not, and what is possible shared). These issues are reflected in the primarily psychological theories and tests of musicality. This article makes an attempt at a Peircean analysis of musicality. It has been suggested that the traditional psychometric approach to musicality is followed by a semiotic approach, and assuming musicality has to do with how subjects make sense in musical processes, the semiotic analysis of musicality is critical. This analysis applies Peirce’s notion of thought-sign and his tenfold classification of the sign (suggesting a three-dimensional exemplification of Peirce’s trichotomous, three dimensional model). The ten classes are differentiated by six transitions, that seem to have their correlates in the psychological understanding of cognition: manifestation, definition, filtering, binding, associating and understanding of the sign. The six transitions appear useful in analyzing the concept of musicality. Correspondingly, the conditions for musical signification extend from ability of auditory sensation to those of dynamical memory, auditory filtering, auditory structuring, association sound objects and ability to understand and manage communicational situations in music. In order to understand musicality, all these aspects should be studied with good ecological and methodological validity in mind.